Dynamics of rumen bacterial composition of yak (Bos grunniens) in response to dietary supplements during the cold season - Ahmad, Anum Ali (PeerJ, 2021)
This study aimed to explore the rumen bacterial community of yak in response to dietary supplements during the cold season. In addition, the rumen fermentation products were also analyzed. Twenty-one female domestic yaks were randomly divided into three groups i.e., pure grazing (GG) group, grazing plus oats hay supplement (OG) group, and grazing plus concentrate supplement group (CG). Rumen contents were collected after 90 days to assess rumen fermentation parameters and bacterial community. The GC group presented higher concentrations of ammonia nitrogen (P < 0.001), and total volatile fatty acids (TVFA) (P < 0.001), and lower rumen pH (P < 0.001) compared to other experimental groups. The CG group displayed higher proportions of propionate, butyrate, isobutyrate, and isovalerate while lower A/P ratio compared to other experimental groups. Shannon, Chao1, and ACE values were significantly lower in the OG group compared to GG and CG groups. Anosim test showed significant differences in bacterial community structure between groups but the PCA plot was not very informative to see these differences. Bacteroidetes, Proteobacteria, and Firmicutes were the three dominant phyla in all groups. The genera Oscillospira was more abundant in GG and OG groups. Higher relative abundance of Ruminococcus and Clostridium was observed in the GG group, while Ruminobacter, Corynebacterium, and Selenomonas were more abundant in the CG group. These findings will help in improving our understanding of rumen bacteria in yaks in response to changes in diet.